1987
DOI: 10.1001/jama.1987.03400040072018
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and Heterosexual Anal Intercourse

Abstract: receptive intercourse had been carried out in the previous two years, needle sharing in the previous five years, and frequency of douching before anal inter¬ course).1 The results indicated signifi¬ cant independent associations between both syphilis (odds ratio = 2-64; F<-001) and race (odds ratio = 2-61; P = -05) and HIV infection. The interaction term for syphilis and race was not significant (P = -31). Thus, Mr Potterat's hypothe¬ sis that syphilis is associated with HIV infection is supported by these dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 2 publications
3
30
0
1
Order By: Relevance
“…Taken together, our results for both humans and rhesus monkeys suggest that primate lentiviruses may gain access to the DC-SIGN ϩ DCs most readily in the intestinal tract, while the thick squamous epithelium serves as a barrier for viral access to DC-SIGN ϩ DCs in the vaginal mucosa. These data are consistent with the observation that the risk of HIV-1 transmission is greater in rectal intercourse than in vaginal exposure (40). Our results also revealed that tissue distribution of DC-SIGN and viral coreceptors is quite similar in humans and in rhesus macaques and further corroborate the validity of this animal model for mucosal HIV-1 transmission studies.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, our results for both humans and rhesus monkeys suggest that primate lentiviruses may gain access to the DC-SIGN ϩ DCs most readily in the intestinal tract, while the thick squamous epithelium serves as a barrier for viral access to DC-SIGN ϩ DCs in the vaginal mucosa. These data are consistent with the observation that the risk of HIV-1 transmission is greater in rectal intercourse than in vaginal exposure (40). Our results also revealed that tissue distribution of DC-SIGN and viral coreceptors is quite similar in humans and in rhesus macaques and further corroborate the validity of this animal model for mucosal HIV-1 transmission studies.…”
supporting
confidence: 91%
“…In contrast, DC-SIGN ϩ CD4 ϩ CCR5 ϩ DCs in the rectal mucosa are separated from the lumen by only a single columnar epithelium, which should allow virus access to DC-SIGN ϩ DCs more easily. This hypothesis is corroborated by the fact that the HIV-1 transmission risk is greater in anal intercourse than in vaginal coitus in women (40).…”
Section: Discussionmentioning
confidence: 81%
“…1,[3][4][5][6][7][8][9] Empirical researches have subsequently demonstrated that anal intercourse carries a higher risk burden than vaginal intercourse even when practiced with a condom. 5,[10][11][12][13] Since condoms are generally manufactured for use in vaginal intercourse, the chances of condom breakage are higher if used in anal sex, thus resulting in an increased risk of exposure to HIV and other STIs. 13,14 Furthermore, a growing body of research also suggests that the high rates of anal cancer could be attributable to the practice of anal intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…At that time, it was considered that HIV was not a dominant problem for the developing world. [13][14][15] Even zero prevalence of HIV was declared among 15,700 prostitutes in Thailand. 13 However, now, large numbers of HIVinfected individuals have been detected in these countries.…”
Section: Resultsmentioning
confidence: 99%